Role of formal input exposure and onset age in grammaticality judgement - Vafa Shojamanesh; Tan, Kim Hua; Khazriyati Salehuddin (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2014)
This study examines the effects of formal input exposure and the onset age of exposure on the performance of eleven different morphosyntactic structures in a foreign language setting. It studies whether being exposed to longer hours of formal language classes at a younger age is advantageous for Iranian EFL learners. Some studies have claimed that there is no advantage for early starters and in the field of grammatical learning, later starters perform better. Four groups of Iranian learners with different formal learning times participated in this study: Groups A and B were public and private school students, respectively, whereas Groups C and D had extra supplementary classes at language institutes as well. A Grammaticality Judgement Task (GJT) including some grammatical structures which were claimed to be problematic for EFL learners, was used as a tool to determine the possible differences in the performance of grammatical structures of the four groups. A two-way ANCOVA and a one-way ANOVA were used to analyse the data. Results suggest that long hours of formal exposure lead to better grammatical performance and the participants who started learning English at age 9 or below performed better in the GJT.